BIOGRAFI SYECH MUHAMMAD ARIF DALAM MENGEMBANGKAN AGAMA ISLAM DI NAGARI LUBUAK GADANG KECAMATAN SANGIR RANTAU DUO BALEH KOTO (1897-1960) - Yandri, Emil Fevy; Kaksim, Kaksim; Ersi, Livia (Pendidikan Sejarah, 2014)
Biography of Syech Muhammad Arif on develops Islam in Nagari Lubuak Gadang, Kecamatan Sangir Rantau Duo Baleh Koto (1897-1960). History Education Program. STKIP PGRI West Sumatera. Padang 2014. This thesis discusses about the struggle ofÂ Syech Muhammad Arif in develop Islam in Kenagarian Lubuak Gadang Kecamatan Sangir Kabupaten Solok Selatan 1897-1960. To facilitate this research, the problem can be formulated as follows: Â how does the process Islam in Kenagarian Lubuak Gadang. How does the role of Syech Muhammad Arif in expanding Islam in Kenagarian Lubuak gadang. How does influence of Syech MuhammadÂ Arif on the society in Kenagarian Lubuak Gadang. This study describes the results: Â The process of development Islam in Kenagarian Lubuak Gadang which doing by Syech Muhammad Arif is with deliver dakwah islamiyah to the whole of Nagari in Kenagarian Lubuak Gadang and remove tahkayul beliefs in that Nagari. Â The big role of Syech Muhammad Arif in development Islam in Kenagarian Lubuak Gadang and persuade the society to move for better life. To fluent his mission Syech Muhammad Arif built mosque and Surau in Kenagarian Lubuak Gadang. The function is for place of worship; learn more about Islam and for resident by his students. Â Influent of Syech Muhammad Arif in develop of Islam in Kenagarian Lubuak Gadang is the society back to the right way and disappear of tahkayul belief , so that make Alqurâan and Sunnah as guide life and now adherent of Islam is growing.